2013
DOI: 10.1007/s12265-013-9525-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sex Differences in Autophagy in the Heart During Coxsackievirus B3-Induced Myocarditis

Abstract: Under normal conditions, autophagy maintains cardiomyocyte health and integrity through turnover of organelles. During stress, oxygen and nutrient deprivation or microbial infection, autophagy prolongs cardiomyocyte survival. Sex differences in induction of cell death may to some extent explain the disparity between the sexes in many human diseases. However, sex differences in gene expression, which regulate cell death and autophagy were so far not taken in consideration to explain the sex bias of viral myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 99 publications
0
18
0
Order By: Relevance
“…), although the nature of the sex effect can differ depending upon cell type, tissue and organism (Koenig et al . ). At the cardiac level, the existence of sex differences in autophagy‐related gene expression was proposed and it was demonstrated that glycogen autophagy is more sensitive to metabolic stress in the hearts of female mice (Reichelt et al .…”
Section: Discussionmentioning
confidence: 97%
“…), although the nature of the sex effect can differ depending upon cell type, tissue and organism (Koenig et al . ). At the cardiac level, the existence of sex differences in autophagy‐related gene expression was proposed and it was demonstrated that glycogen autophagy is more sensitive to metabolic stress in the hearts of female mice (Reichelt et al .…”
Section: Discussionmentioning
confidence: 97%
“…83 Sex-dependent differences in autophagic responses have been shown before. [84][85][86][87] In a mouse model of cancer-induced cardiac atrophy, Cosper et al 84 found that males have a more severe phenotype than females, including greater cardiac autophagy. Sexual dimorphism was also found in neuronal response to nutrient deprivation with neurons from males but not females undergoing autophagy.…”
Section: Malesmentioning
confidence: 99%
“…In humans, women show less apoptosis and less maladaptive remodeling relative to men in response to acute coronary ischemia [206]. Under normal conditions men’s hearts have increased expression of CARBONIC ANHYDRASE 3 , a gene associated with hypertrophy and heart failure, and decreased expression of APOJ/CLUSTERIN , an autophagy regulator thought to be protective upon inflammatory injury [207]. Studies of human cells and rodent models indicate that estrogen is generally protective but may not be responsible for all the sex differences in heart stress responses.…”
Section: Sex-specific Autophagy and Apoptosis In Mammalian Cells And mentioning
confidence: 99%